The Features of Jordanian Song's Development from Popular form to Traditional in the Works of Mohammed Wahib - Aziz Madi; Safa' Haddad (My University, 2016)
This research aims to study the features of the of Jordanian song’sdevelopment from folk form to the popular one, in the songs of the Jordanian artist Mohammed Wahib, through studying the factors that contributed to give it a renewed meaning, and made it no longer be fall under the title of “folk song”, take into consideration the folk song its original and specificity which made it the core of the Jordanian music and singing. The study presents an overview of the Arab singing and other more detailed of Jordanian song, and discusses the dialectic of folk and traditional; that the Jordanian song has been subjected to it since it has been limited under the title of Folk song. The study includes selected samples of the Jordanian artist Mohammed Wahib, who is one of the most famous and pioneers of Jordanian Song, by providing great works; which allows the opportunity to follow the development of the Jordanian song since its beginnings, and through the review of Wahib’s emergence, study his songs, comparing the musical features and the characteristics of his works, and identify its position between popular (folk) and traditional, and thus determine the features of development through his songs.

يهدف هذا البحث إلى دراسة ملامح تطور الأغنية الأردنية من الشعبية إلى التقليدية (الدارجة) في أعمال الفنان الأردني محمد وهيب، وذلك من خلال دراسة العوامل التي أسهمت في إكساب الأغنية معنى متجددا؛ لتتسع أكثر في معناها ومحتواها، وتخرج من تحت العنوان العريض الذي لطالما انحسرت تحته؛ ألا وهو "الأغنية الشعبية" (الفلكلورية)، آخذين بعين الاعتبار أهمية الأغنية الشعبية وعراقتها وخصوصيتها، التي جعلت منها جوهر الموسيقا والغناء الأردني. تعرض هذه الدراسة لمحة عن الغناء العربي وأخرى أكثر تفصيلا عن الأغنية الأردنية، وتناقش جدلية الشعبية (الفلكلورية) والتقليدية (الدارجة)؛ التي تخضع لها الأغنية الأردنية مذ كانت تقتصر في مضمونها ومظهرها على الشعبية البحتة. تتناول هذه الدراسة عينة مختارة من أغاني الفنان الأردني محمد وهيب، الذي يعد من أبرز رواد الأغنية الأردنية ممن قدموا أعمالا غنائية قيمة؛ والتي تتيح الفرصة للتتبع مراحل تطور الأغنية الأردنية منذ بداياتها، وذلك من خلال استعراض مسيرة الفنان محمد وهيب، ودراسة أغنياته، وملاحظة مدى قربها أو بعدها عن خصوصية الأغنية الشعبية الأردنية، ومقارنة الخصائص والسمات الموسيقية والفنية لأعماله، وتحديد موقعها ما بين الشعبية (الفلكلورية) والتقليدية (الدارجة)، وبالتالي تحديد ملامح التطور التي تبرز من خلال أعماله الغنائية.
سمات التطور في الأغنية الأردنية من الشعبية إلى التقليدية في أعمال الفنان محمد وهيب